The Effects of Different Rates of Polyethylene Bags Openings on Storage of ‘Sultana Seedless’ Grape Variety - Ayşe Bayramoğlu; Fatih Şen (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to determine the effects of different openings onto the polyethylene (PE) packages used in storage of ‘Sultani Çekirdeksiz’ grape variety on quality, SO2 damage, pathological and physiological disorders of grapes. Grapes were harvested at full maturity and placed in PE bags with ‰0 (control), ‰0.5, ‰1 and ‰2 openings. After pre-cooling grapes in the case of SO2 pets were placed after the mouth of the bags were closed. Grapes were stored at 0°C and 90-95% relative humidity for 4 months, and quality changes were determined in monthly samples. SO2 concentrations detected at the end of storage in PE packages with ‰0, ‰0.5, ‰1 and ‰2 openings were 11.16, 5.80, 2.05 and 0,00 mg/kg respectively. It has been found that grapes in packages without opening had significant SO2 content and SO2 damage, especially the end of storage. However, grapes in packages with ‰2 openings had high weight loss and browning scores in stems. The results showed that ‘Sultani Çekirdeksiz’ grapes could be stored more successfully in PE packages with ‰0.5 openings. ‘Sultani Seedless’ grape variety, it may be suggested to use PE bags without openings for 2 and 3 months storage.